Representasi Maskulinitas Pria dalam Iklan Televisi Men’s Biore Cool Oil Clear - Rezki Pratami; Togi Prima Hasiholan (Jurnal Komunikasi, 2020)
The purpose of this research is to analyze the meaning contained in Men’s Biore Cool Oil Clear advertisement in three different versions namely version #BeMagnetic 2019, #RefreshSangatLo! 2018, and Long Riding 2017, and discuss the myths and male masculinity representation by using Roland Barthes's semiotic theory. The results showed that the three ads represent men into 8 myths, namely Men as free creatures, Men as good-looking creatures, Men as charismatic creatures, Men as leaders, Men as optimistic beings, Men as rulers, and Men as narcissist beings. The masculine traits contained are Give em Hell, Metrosexual, Be a Big Wheel, Be a Sturdy Oak, and New man as narcissist. The message of masculinity formed is an easy way to wash face to be able to become a masculine, namely men who pay attention to cleanliness and appearance of themselves, which opens new perspectives in the wider community over the stereotypes of masculine images that have been circulating.